2021
DOI: 10.3390/cimb43020056
|View full text |Cite
|
Sign up to set email alerts
|

Interactome Analysis of KIN (Kin17) Shows New Functions of This Protein

Abstract: KIN (Kin17) protein is overexpressed in a number of cancerous cell lines, and is therefore considered a possible cancer biomarker. It is a well-conserved protein across eukaryotes and is ubiquitously expressed in all cell types studied, suggesting an important role in the maintenance of basic cellular function which is yet to be well determined. Early studies on KIN suggested that this nuclear protein plays a role in cellular mechanisms such as DNA replication and/or repair; however, its association with chrom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 66 publications
0
6
0
Order By: Relevance
“…Interactors that were lost upon PFI-7 treatment included RNA helicases DDX17, DDX21, and DDX50 that have previously been reported to associate with the CTLH complex 16,18,34,36 , and that we now show are GID4-dependent interactors. Indeed, many of the direct GID4 interactors are nucleolar proteins including DDX21 39 , DDX50 40 , and KIN 41 , among others. This points to possible nucleolar-specific functions of the CTLH complex that have been suggested previously 36 and remain to be elucidated further.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interactors that were lost upon PFI-7 treatment included RNA helicases DDX17, DDX21, and DDX50 that have previously been reported to associate with the CTLH complex 16,18,34,36 , and that we now show are GID4-dependent interactors. Indeed, many of the direct GID4 interactors are nucleolar proteins including DDX21 39 , DDX50 40 , and KIN 41 , among others. This points to possible nucleolar-specific functions of the CTLH complex that have been suggested previously 36 and remain to be elucidated further.…”
Section: Discussionmentioning
confidence: 99%
“…Intriguingly, PFI-7 treatment decreased levels of several proteins including KIN. KIN is a DNA and RNA binding protein implicated in ribosome biogenesis whose interactome shares several interactors with GID4, including DDX50 41 . There are several plausible explanations for how GID4 antagonism by PFI-7 might lead to decreased protein abundance.…”
Section: Discussionmentioning
confidence: 99%
“…In past studies, we didn't discover how KIN17 regulates EMT in tumor cells. However, through the protein–protein interaction network and bioinformatics of KIN17, we have found that KIN17 is likely to interact with Smad2 31 . Smad2 is an important factor of TGF‐β pathway, so we speculated that KIN17 induced EMT through the TGF‐β/Smad2 pathway 18 .…”
Section: Discussionmentioning
confidence: 94%
“…However, through the protein-protein interaction network and bioinformatics of KIN17, we have found that KIN17 is likely to interact with Smad2. 31 Smad2 is an important factor of TGF-β pathway, so we speculated that KIN17 induced EMT through the TGF-β/Smad2 pathway. 18 Here, we first verified that the expression of Smad2 and P-Smad2 protein changed with the change After 24 h, we observed that the cells migration and invasion ability, and the expression levels of p-Smad2 and EMT-related proteins were rescued.…”
Section: Discussionmentioning
confidence: 97%
“…New interactions between KIN17 and other proteins have also been found, particularly proteins related to RNA processing, such as certain proteins associated with pre-mRNA splicing and ribosome biogenesis (Fig. 3) (29).…”
Section: Kin17 a Dna And Rna Binding Proteinmentioning
confidence: 99%